Design and implementation of quality inspection information management system based on Cloud Native - Chen Bo; Wu Yunfeng; Lu Kai (Dianzi Jishu Yingyong, 2022)
With the complexity of quality inspection information management business，the existing quality inspection information management systems have so many problems, such as insufficient processing capacity for big data, high manual operation error ratio and poor scalability. This paper proposed a quality inspection information management system based on Cloud Native, then analyzed and researched on the Cloud Native technology, and clarified the principles and characteristics of Cloud Native technology. Combined with the actual use of quality inspection information management business, the Cloud-Native-based quality inspection information management system was designed and implemented in detail. Finally, the function and performance of the system were tested to verify the effectiveness of the overall design scheme.